2018
DOI: 10.1097/md.0000000000013296
|View full text |Cite
|
Sign up to set email alerts
|

Ability of preschoolers to achieve maximal exercise and its correlation with oxygen uptake efficiency slope ∼ an observational study by direct cardiopulmonary exercise testing

Abstract: The oxygen uptake efficiency slope (OUES) is a well-established substitute for maximum oxygen uptake ( O2 max) in submaximal exercise effort among adolescents and adults. Few studies have analyzed the exercise capacity (EC) and OUES of children aged 4 to 6 (preschoolers). Body fat has been proved to negatively affect EC among schoolchildren. The purposes of this study were to assess the capacity of preschoolers in achieving O2 max and evaluate the correlation of peak metabolic equivalent (peak MET) and peak o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
(37 reference statements)
1
8
0
1
Order By: Relevance
“…In our study, we observed that even in preschool children with normal body adipose, there was around 20% (no matter by which classifications) participants could not reach maximal effort during exercise testing. Few studies in children aged less than 7 years old had proved that they had poorer ability to perform maximal effort as similar as out results[19, 39]. What is more, we also found that preschool children with excess body adipose had significant lower percentage to achieve maximal effort than those with normal body adipose by BMI and FFMI classifications.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In our study, we observed that even in preschool children with normal body adipose, there was around 20% (no matter by which classifications) participants could not reach maximal effort during exercise testing. Few studies in children aged less than 7 years old had proved that they had poorer ability to perform maximal effort as similar as out results[19, 39]. What is more, we also found that preschool children with excess body adipose had significant lower percentage to achieve maximal effort than those with normal body adipose by BMI and FFMI classifications.…”
Section: Discussionsupporting
confidence: 88%
“…OUES-100 has been proved to correlate strongly with peak O 2 in healthy children aged more than seven years old[41]. It our past study, we found that OUES correlated positive-moderately with peak MET and peak VO2 in preschool children older than 4 years old[19]. Many studies had shown that health-related physical fitness is associated with total and central body fat among preschoolers[18, 42] but little available studies assessed preschoolers’ CRF by CPET.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations